Researching complex projects: Using causal mapping to take a systems perspective - Ackermann, Fran; Alexander, J. (Pergamon, 2016)
Extant literature has called for researchers to be more pluralistic in their approaches to researching projects. Responding to this call, this paper offers an exposition of a causal mapping technique. In the project management literature, there already exists a small number of articles reporting effective use of causal mapping. However, these are not dedicated to detailed explanation of the technique itself and so lack consideration of its features beyond those relevant to a particular application. Consequently, an exposition of the technique is needed to enable comprehensive understanding of causal mapping to be gained and its suitability for research designs assessed. Specifically, this paper examines causal mapping's theoretical grounding, explores its strengths and weakness, presents example applications, compares alternative causal mapping approaches, and overall, explains how causal mapping can support a systemic perspective on projects. These issues will be of interest to researchers who wish to incorporate causal mapping into their project management research designs.